A 3D-graphene fiber electrode embedded with nitrogen-rich-carbon-coated ZIF-67 for the ultrasensitive detection of adrenaline. Issue 35 (29th August 2019) - Zeng, Jinfeng; Xu, Ruoyu; Jiao, Le; Wang, Yuze; Chen, Liwei; Windle, Christopher D.; Ding, Xiaoteng; Zhang, Zhipan; Han, Qing; Qu, Liangti
Abstract : A novel nitrogen-rich-carbon-coated ZIF-67 embedded three-dimensional-graphene (ZIF-67/NC/3DG) fiber is successfully synthesized for effectively detecting adrenaline. Abstract : A novel nitrogen-rich-carbon-coated ZIF-67 embedded three-dimensional-graphene (ZIF-67/NC/3DG) fiber was fabricated via a facile one-pot electrodeposition self-assembly method, and used as a prominent electrode for the non-enzymatic detection of adrenaline (Ad). In this design, the prepared ZIF-67 adsorbs Ad through hydrogen bonding and electrostatic interaction, while polypyrrole functions as the precursor of the conductive NC that seamlessly connects ZIF-67 with the 3DG fiber electrode to ameliorate the poor conductivity of the ZIF-67 moiety and thus improve the sensitivity of the ZIF-67/NC/3DG fiber electrode for detecting Ad. The constructed fiber sensor shows a double linear response over the Ad concentration range of 0.06–95 μM with a high sensitivity of 44.6 mA mM −1 cm −2 and 95.0–5900 μM with a good sensitivity of 11.0 mA mM −1 cm −2, giving a low detection limit of 0.02 μM and excellent repeatability. The ZIF-67/NC/3DG fiber electrode was further successfully applied for the determination of Ad in a real sample of human serum, indicating that this fiber electrode is a promising miniaturized sensor for electrochemical analysis.